A covalent organic framework material with a helical structure and a preparation method thereof
Through the condensation reaction of 2,4,6-trihydroxy-1,3,5-benzenetrialdehyde and hydrazine hydrate, combined with the regulation of acetic acid and surfactant, the helical structure COF was successfully synthesized under an anchiral element, and the hand was solved The problem of sexual element dependence has achieved highly controllable COF synthesis and flexible structural adjustment.
Patent Information
- Application Number
- CN202411231125.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, chiral elements or environment are required for the synthesis of helical covalent organic frame materials (COFs), and the controllable synthesis of chiral nanostructures poses great challenges and is difficult to achieve in an achiral system.
Through the condensation reaction of 2,4,6-trihydroxy-1,3,5-benzenetrialdehyde and hydrazine hydrate, combined with the regulation of acetic acid and surfactant, a helical structure COF without chiral elements was prepared, overcoming chirality Factors limit and control the pitch and helical distribution of the material by adjusting the acetic acid volume fraction and surfactant type.
It realizes highly controllable synthetic helical structure COF in achiral elements and environments, breaks away from the use of chiral monomers, catalysts or templates, and has wider application potential and flexibility.
Smart Images

Figure CN118725222B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of covalent organic framework materials, and in particular relates to a covalent organic framework material with a helical structure and a preparation method thereof. Background Art
[0002] In the past decade, covalent organic framework (COF) nanostructures have attracted extensive research interests in multiple fields because of their remarkable diversity in nanoscale morphology, pore structure, and chemical composition, which enable them to have excellent dispersibility, enhanced active site accessibility, and flexible design of synergy between guest materials and functional framework materials. In order to fully realize the potential of COF materials, researchers have conducted a lot of work to achieve precise control of their morphology and optimization of nanostructures. Among these nanostructures, COFs with helical geometry show great application potential in biology, physics, and materials science, so it is particularly important to develop a method to easily construct COF helical nanostructures.
[0003] The generation of helical structures at different length scales is usually achieved through the assembly of non-centrosymmetric building blocks or under the action of chiral fields or chiral templates. Therefore, it is crucial to introduce appropriate chiral elements into the reaction system when designing COF helical nanostructures. In recent years, researchers have successfully synthesized several new chiral COFs by polymerization of enantiomeric monomers or in situ chirality induction using chiral catalysts or chiral templates. However, the construction of COFs with helical nanostructures using achiral monomers in achiral synthetic systems has not yet been achieved. In addition, in all previous studies on the synthesis of helical COFs, the controllable synthesis of chiral nanostructures remains a huge challenge. Therefore, it is imperative to develop novel methods for highly controllable COF chiral materials that do not rely on chiral assembly elements or environments. Summary of the invention
[0004] In order to solve the above-mentioned defects existing in the prior art, the present invention provides a covalent organic framework material with a helical structure and a preparation method thereof. The method synthesizes a covalent organic framework (COF) helical nanoribbon through a condensation reaction of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde (Tp) and hydrazine hydrate; the assembly elements and the environment are not chiral, which overcomes the limitation that the helical material can only be synthesized in the presence of chiral factors; in addition, the pitch of the material and the distribution of the helix on the nanomaterial can be adjusted by adjusting the volume fraction of acetic acid and the type of surfactant.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing a covalent organic framework material with a helical structure specifically comprises the following steps:
[0007] Step 1: Preparation of organic mixed solvent;
[0008] Acetic acid, water and mesitylene are mixed in a certain proportion to obtain an organic mixed solvent;
[0009] Step 2: dissolving the surfactant in an organic mixed solvent;
[0010] Step 3: adding 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde and hydrazine hydrate in a certain proportion to the mixed solution obtained in step 2;
[0011] Step 4: Preparation of covalent organic polymer;
[0012] The mixed solution obtained in step 3 is stirred at room temperature, and after sufficient reaction, is centrifuged, washed and dried to obtain a covalent organic polymer;
[0013] Step 5: Preparation of helical covalent organic framework materials;
[0014] The covalent organic polymer obtained in step 4 is added to a glass tube, an organic solvent is added, and then a catalyst is added. The glass tube is placed in liquid nitrogen for freezing, the tube is sealed with a vacuum flame, and finally placed in an oven for heating. At the end of the reaction, the solid product is collected by centrifugation and washed; the washed solid product is dried under vacuum to obtain a covalent organic framework material with a helical structure.
[0015] Furthermore, in step 1, the surfactant is F127 or F108 or Brij 56, and the mass percentage of the surfactant in the mixed solvent is 0.5-5 w%.
[0016] Furthermore, in step three, the molar ratio of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde to hydrazine hydrate is 1:3, wherein the molar concentration of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde in the mixed solvent is 5-30 mM.
[0017] Furthermore, in step 4, the stirring rate is 500 rpm; the reaction time is 4 h; the centrifugal speed is 4000 rpm, and the time is 3 min; the washing solvent is ethanol; and the drying temperature is 60 °C.
[0018] Furthermore, in step five, the organic solvent is a mixed solvent of mesitylene and 1,4-dioxane; the catalyst is an acetic acid aqueous solution, and the concentration of the acetic acid aqueous solution is 6M; the heating temperature is 120°C, and the reaction time is 3 days.
[0019] Furthermore, in step five, the centrifugal speed is 4000 rpm, the time is 3 min; the washing solvent is ethanol, tetrahydrofuran and acetone; and the drying temperature is 80°C.
[0020] On the other hand, the present invention also provides a covalent organic framework material with a helical structure, which is prepared by the above preparation method.
[0021] Compared with the prior art, the advantages of the present invention are as follows:
[0022] 1. The present invention synthesizes a series of helical covalent organic framework materials for the first time based on 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde and hydrazine hydrate without any chiral elements and environment, and gets rid of the use of chiral monomers, chiral catalysts or templates;
[0023] 2. The present invention establishes for the first time a reaction system related to the synthesis of helical covalent organic framework materials;
[0024] 3. The synthesis method established in the present invention is highly controllable. By changing the volume fraction of acetic acid or the type of surfactant, a series of COFs with different pitches and different helical distributions are synthesized, which is impossible to achieve with previous chiral COF synthesis methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific implementation of the present invention or the technical solution in the prior art, the drawings required for use in the specific implementation or the description of the prior art are briefly introduced below.
[0026] Figure 1 The scanning and transmission images of COP HNRs-32 synthesized in Example 1;
[0027] Among them, a is a low-magnification scanning picture of COP HNRs-32 synthesized by the present invention, b is a low-magnification transmission picture of COPHNRs-32 synthesized by the present invention, c is a single scanning picture of COP HNRs-32 synthesized by the present invention, and d is a single transmission picture of COP HNRs-32 synthesized by the present invention;
[0028] Figure 2 The powder X-ray diffraction spectra of COP HNRs-32 and raw material monomers synthesized in Example 1 and the simulated X-ray diffraction spectra;
[0029] Figure 3 The Fourier transform infrared spectra of the COP HNRs-32 synthesized in Example 1 and the raw material monomers;
[0030] Figure 4 This is the solid-state NMR spectrum of COP HNRs-32 synthesized in Example 1;
[0031] Figure 5 The morphology characterization diagram, morphology schematic diagram and element distribution diagram of the COF HHNRs-32 synthesized by the present invention;
[0032] Among them, a is a low-magnification scanning image of COF HHNRs-32 synthesized by the present invention, b is a high-magnification scanning image of COFHHNRs-32 synthesized by the present invention, c is a low-magnification transmission image of COF HHNRs-32 synthesized by the present invention, d is a high-magnification transmission image of COF HHNRs-32 synthesized by the present invention, e is a conformational image of the synthesized spiral material at different viewing angles and a schematic diagram of the cavity, pitch and nanoshell, f is a schematic diagram of right-handed COF HHNRs-32, g is a scanning image of a single right-handed COF HHNRs-32, h is a transmission image of a single right-handed COF HHNRs-32, i is a schematic diagram of left-handed COF HHNRs-32, j is a scanning image of a single left-handed COFHHNRs-32, k is a transmission image of a single left-handed COF HHNRs-32, and l is an element distribution map of COF HHNRs-32;
[0033] Figure 6 The powder X-ray diffraction spectrum of COF HHNRs-32 synthesized in Example 1 and the refined and simulated X-ray diffraction spectrum;
[0034] Figure 7 The Fourier transform infrared spectra of the COF HHNRs-32 and the raw material monomer synthesized in Example 1;
[0035] Figure 8 This is the solid-state NMR spectrum of COF HHNRs-32 synthesized in Example 1;
[0036] Fig. 9 is a diagram of the pitch change regulated by adjusting the concentration of acetic acid; wherein, a is a schematic diagram of regulating the pitch of the material by adjusting the amount of acetic acid, b is a low-magnification transmission image of COF HHNRs-32 synthesized by the present invention, c is a single scanned image of COF HHNRs-32 synthesized by the present invention, d is a single transmittance image of COF HHNRs-32 synthesized by the present invention, e is a low-magnification transmission image of COF HHNRs-24 synthesized by the present invention, f is a single scanned image of COF HHNRs-24 synthesized by the present invention, g is a single transmittance image of COF HHNRs-24 synthesized by the present invention, h is a low-magnification transmission image of COF HHNRs-8 synthesized by the present invention, i is a single scanned image of COF HHNRs-8 synthesized by the present invention, and j is a single transmittance image of COF HHNRs-8 synthesized by the present invention;
[0037] Fig.10Schematic diagram of the synthesis of COP HNRs-F108, COP HNRs-Brij 56, COF HNRs-F108 and COF HNRs-Brij 56 synthesized in Examples 1-5, and the corresponding scanning and transmission images. DETAILED DESCRIPTION
[0038] In order to clearly and completely describe the technical solution and its specific working process of the present invention, the specific implementation methods of the present invention are as follows in conjunction with the accompanying drawings of the specification:
[0039] Example 1: This example provides a method for preparing a helical covalent organic framework material, wherein COF HHNRs-32 is synthesized under the condition that the volume fraction of acetic acid is 32%, and specifically comprises the following steps:
[0040] 150 mg of surfactant F127 was dissolved in a mixed solution of 3.2 mL of acetic acid, 6.8 mL of water and 0.1 mL of mesitylene, and then 21 mg of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde (0.1 mmol) and 10 μL of hydrazine hydrate (0.15 mmol) were added; the mixture was stirred at 500 rpm for 4 h at room temperature, and after sufficient reaction, the solid product was collected by centrifugation at 4000 rpm for 3 min, washed three times with ethanol, and dried at 60 °C overnight to obtain the covalent organic polymer product COPHNRs-32. 24 mg of the covalent organic polymer prepared above was added to a glass tube, 0.75 mL of mesitylene and 0.25 mL of 1,4-dioxane were added, and 0.34 mL of acetic acid aqueous solution (3 M) was added as a catalyst, the glass tube was frozen in liquid nitrogen, the tube was sealed with a vacuum flame, and finally heated in a 120 °C oven for 3 days. At the end of the reaction, the solid product was collected by centrifugation at 4000 rpm for 3 min, washed with ethanol, tetrahydrofuran and acetone respectively, and the thoroughly washed product was dried at 80 °C under vacuum overnight to obtain the covalent organic framework material COF HHNRs-32 with a helical structure.
[0041] like Figure 1 As shown in the scanning and transmission images, the COP HNRs-32 synthesized in this example has a smooth surface;
[0042] Figure 2 The powder X-ray diffraction spectra of the COP HNRs-32 and the raw material monomers synthesized in this example and the simulated X-ray diffraction spectra reveal that it is an amorphous polymer;
[0043] like Figure 3The Fourier transform infrared spectra of the synthesized COP HNRs-32 and the raw material monomers are shown in Figure 1. -1 The disappearance of the carbonyl stretching band at 1592 cm -1 The formation of C=C and C=N bonds at the sites proves the occurrence of polymerization.
[0044] like Figure 4 Shown is the solid-state NMR spectrum of COP HNRs-32, which also reveals the occurrence of polymerization reaction;
[0045] Figure 5 Figures ad are scanning and transmission images of the COF HHNRs-32 synthesized in this example, indicating that hollow spiral nanobelts are formed after the polymer is crystallized, and the surface of the nanobelts is rough and is composed of small particles aggregated; Figure 5 e is the conformational diagram of the synthesized helical material at different viewing angles and the schematic diagram of the cavity, helical pitch and nanoshell; Figure 5 f is a schematic diagram of right-handed COF HHNRs-32, Figure 5 g is a scanning image of a single right-handed COF HHNRs-32. Figure 5 h is the transmission image of a single right-handed COF HHNRs-32. Figure 5 i is a schematic diagram of the left-handed COF HHNRs-32, Figure 5 j is a scanned image of a single left-handed COF HHNRs-32. Figure 5 k is a transmission image of a single left-handed COF HHNRs-32, indicating that the COF HHNRs-32 synthesized in this example contains both left-handed and right-handed COF HHNRs-32; l is an element distribution diagram of COF HHNRs-32, indicating that carbon, oxygen and nitrogen elements are uniformly distributed in COF HHNRs-32;
[0046] like Figure 6 The powder X-ray diffraction spectrum of COFHHNRs-32 synthesized in this example and the powder X-ray diffraction spectrum of Rietveld refinement shown in FIG. 1 show that the method of this example successfully synthesized a P6 Two-dimensional covalent organic framework materials of space groups;
[0047] Figure 7 The Fourier transform infrared spectra of the COF HHNRs-32 synthesized in this example and the raw material monomer are shown in Figure 1. Compared with the monomer Tp, the infrared spectrum of COF HHNRs-32 has a peak at 1592 cm -1 The characteristic stretching bands originating from C=C and C=N bonds, as well as the disappearance of the stretching bands from the monomeric carbon groups, together confirm the formation of COF;
[0048] Figure 8 The solid-state NMR spectrum of the COF HHNRs-32 shown shows resonance signals of the keto carbon (180 ppm), imine carbon, and enol carbon (166 ppm), indicating the coexistence of enol and keto structures in the organic matrix.
[0049] Example 2: This example provides a method for preparing a helical covalent organic framework material, wherein COF HHNRs-24 is synthesized under the condition that the volume fraction of acetic acid is 24%, and specifically comprises the following steps:
[0050] 150 mg of surfactant F127 was dissolved in a mixed solution of 2.4 mL of acetic acid, 7.6 mL of water and 0.1 mL of mesitylene, and then 21 mg of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde (0.1 mmol) and 10 μL of hydrazine hydrate (0.15 mmol) were added. The mixture was stirred at 500 rpm for 4 h at room temperature. After sufficient reaction, the solid product was collected by centrifugation at 4000 rpm for 3 min, washed three times with ethanol, and dried at 60 °C overnight to obtain the covalent organic polymer product COPHNRs-24. 24 mg of the covalent organic polymer prepared above was added to a glass tube, 0.75 mL of mesitylene and 0.25 mL of 1,4-dioxane were added, and 0.34 mL of acetic acid aqueous solution (3 M) was added as a catalyst. The glass tube was frozen in liquid nitrogen, vacuum-sealed with a flame, and finally heated in a 120 °C oven for 3 days. At the end of the reaction, the solid product was collected by centrifugation at 4000 rpm for 3 min, washed with ethanol, tetrahydrofuran and acetone respectively, and the thoroughly washed product was dried at 80 °C under vacuum overnight to obtain the covalent organic framework material COF HHNRs-24 with a helical structure.
[0051] Example 3: This example provides a method for preparing a helical covalent organic framework material, wherein COF HHNRs-8 is synthesized under the condition that the volume fraction of acetic acid is 8%, and specifically comprises the following steps:
[0052] 150 mg of surfactant F127 was dissolved in a mixed solution of 0.8 mL of acetic acid, 9.2 mL of water and 0.1 mL of mesitylene, and then 21 mg of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde (0.1 mmol) and 10 μL of hydrazine hydrate (0.15 mmol) were added. The mixture was stirred at 500 rpm for 4 h at room temperature. After sufficient reaction, the solid product was collected by centrifugation at 4000 rpm for 3 min, washed three times with ethanol, and dried at 60 °C overnight to obtain the covalent organic polymer product COPNRs-8. 24 mg of the covalent organic polymer prepared above was added to a glass tube, 0.75 mL of mesitylene and 0.25 mL of 1,4-dioxane were added, and 0.34 mL of acetic acid aqueous solution (3 M) was added as a catalyst. The glass tube was frozen in liquid nitrogen, vacuum-sealed with a flame, and finally heated in a 120 °C oven for 3 days. At the end of the reaction, the solid product was collected by centrifugation at 4000 rpm for 3 min, washed with ethanol, tetrahydrofuran and acetone respectively, and the thoroughly washed product was dried at 80 °C under vacuum overnight to obtain the covalent organic framework material COF HNRs-8 with a helical structure.
[0053] like Fig. 9 As shown, it is shown that the pitch of the COF material changes with the change of the volume fraction of acetic acid, and the smaller the volume fraction of acetic acid, the larger the pitch, until there is no spiral feature in the end.
[0054] Example 4: This example provides a method for preparing a helical covalent organic framework material, wherein COF HNRs-F108 is synthesized under the condition that the surfactant is F108, and specifically comprises the following steps:
[0055] 150 mg of surfactant F108 was dissolved in a mixed solution of 3.2 mL of acetic acid, 6.8 mL of water and 0.1 mL of mesitylene, and then 21 mg of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde (0.1 mmol) and 10 μL of hydrazine hydrate (0.15 mmol) were added. The mixture was stirred at 500 rpm for 4 h at room temperature. After sufficient reaction, the solid product was collected by centrifugation at 4000 rpm for 3 min, washed three times with ethanol, and dried at 60 °C overnight to obtain the covalent organic polymer product COPHNRs-F108. 24 mg of the covalent organic polymer prepared above was added to a glass tube, 0.75 mL of mesitylene and 0.25 mL of 1,4-dioxane were added, and 0.34 mL of acetic acid aqueous solution (3 M) was added as a catalyst. The glass tube was frozen in liquid nitrogen, vacuum-sealed with a flame, and finally heated in a 120 °C oven for 3 days. At the end of the reaction, the solid product was collected by centrifugation at 4000 rpm for 3 min, washed with ethanol, tetrahydrofuran and acetone respectively, and the thoroughly washed product was dried at 80 °C under vacuum overnight to obtain the covalent organic framework material COF HNRs-F108 with a helical structure.
[0056] Example 5: This example provides a method for preparing a helical covalent organic framework material, wherein COF HNRs-Brij 56 is synthesized under the condition that the surfactant is Brij 56, and specifically comprises the following steps:
[0057] 150 mg of surfactant Brij 56 was dissolved in a mixed solution of 2.4 mL of acetic acid, 7.6 mL of water and 0.1 mL of mesitylene, and then 21 mg of 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde (0.1 mmol) and 10 μL of hydrazine hydrate (0.15 mmol) were added. The mixture was stirred at 500 rpm for 4 h at room temperature. After sufficient reaction, the solid product was collected by centrifugation at 4000 rpm for 3 min, washed three times with ethanol, and dried at 60 °C overnight to obtain the covalent organic polymer product COPHNRs-Brij 56. 24 mg of the covalent organic polymer prepared above was added to a glass tube, 0.75 mL of mesitylene and 0.25 mL of 1,4-dioxane were added, and 0.34 mL of acetic acid aqueous solution (3 M) was added as a catalyst. The glass tube was frozen in liquid nitrogen, vacuum-sealed with a flame, and finally heated in a 120 °C oven for 3 days. At the end of the reaction, the solid product was collected by centrifugation at 4000 rpm for 3 min, washed with ethanol, tetrahydrofuran and acetone respectively, and the thoroughly washed product was dried at 80 °C under vacuum overnight to obtain the covalent organic framework material COF HNRs-Brij 56 with a helical structure.
[0058] Fig.10 Schematic diagram of the synthesis of COP HNRs-F108, COP HNRs-Brij 56, COF HNRs-F108 and COF HNRs-Brij 56, as well as the corresponding scanning and transmission images, indicating that the position of the helix on the nanomaterial changes by changing the type of surfactant.
[0059] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0060] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0061] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a helical covalent organic framework material, characterized in that: The specific steps include: Step 1: Preparation of organic mixed solvent; Acetic acid, water and mesitylene are mixed in a certain proportion to obtain an organic mixed solvent; The volume of acetic acid and water is 10 mL, the volume of mesitylene is 0.1 mL, and the volume of acetic acid and water is 3.2 mL and 6.8 mL, 2.4 mL and 7.6 mL, or 0.8 mL and 9.2 mL. Step 2: dissolving the surfactant in an organic mixed solvent; Step 3: adding 2,4,6-trihydroxy-1,3,5-benzenetricarboxaldehyde and hydrazine hydrate in a certain proportion to the mixed solution obtained in step 2; Step 4: Preparation of covalent organic polymer; The mixed solution obtained in step 3 is stirred at room temperature, and after sufficient reaction, is centrifuged, washed and dried to obtain a covalent organic polymer; Step 5: Preparation of helical covalent organic framework materials; The covalent organic polymer obtained in step 4 is added to a glass tube, an organic solvent is added, and then a catalyst is added, the glass tube is placed in liquid nitrogen for freezing, the tube is sealed with a vacuum flame, and finally placed in an oven for heating. At the end of the reaction, the solid product is collected by centrifugation and washed; the washed solid product is dried under vacuum to obtain a covalent organic framework material with a helical structure; In step 1, the surfactant is F127 or F108 or Brij 56, and the mass percentage of the surfactant in the mixed solvent is 0.5-5w%; In step 5, the organic solvent is a mixed solvent of mesitylene and 1,4-dioxane; the catalyst is an acetic acid aqueous solution, and the concentration of the acetic acid aqueous solution is 6M; the heating temperature is 120°C, and the reaction time is 3 days; In step 3, the molar ratio of 2,4,6-trihydroxy-1,3,5-benzenetricarbaldehyde to hydrazine hydrate is 1:3, wherein the molar concentration of 2,4,6-trihydroxy-1,3,5-benzenetricarbaldehyde in the mixed solvent is 5-30 mM.
2. The method for preparing a helical covalent organic framework material according to claim 1, characterized in that: In step 4, the stirring rate is 500 rpm; the reaction time is 4 hours; the centrifugal speed is 4000 rpm, and the time is 3 minutes; the washing solvent is ethanol; and the drying temperature is 60°C.
3. The method for preparing a helical covalent organic framework material according to claim 1, characterized in that: In step 5, the centrifugal speed is 4000 rpm, the time is 3 min; the washing solvents are ethanol, tetrahydrofuran and acetone; and the drying temperature is 80°C.
4. A helical covalent organic framework material, characterized in that: The method is prepared by any one of claims 1 to 3.
Citation Information
Patent Citations
Long alkyl chain modified covalent organic framework material as well as preparation method and application thereof
CN115260423A
Two-dimensional imino covalent organic framework material as well as preparation method and application thereof
CN116535588A
Covalent organic framework photocatalyst containing bithiazole structure and preparation method of covalent organic framework photocatalyst
CN116535594A
Covalent organic framework material with spiral chirality as well as preparation method and application of covalent organic framework material
CN117402308A
Green solid-phase synthesis method for covalent organic framework material
WO2023124952A1
